The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.16986/huje.2019052510
|View full text |Cite
|
Sign up to set email alerts
|

Araştırmaya Dayalı Öğrenme Stratejisinin Öğrencilerin Akademik Başarılarına Etkisi: Bir Meta Analiz Çalışması

Abstract: Bu çalışmada araştırmaya dayalı öğrenme stratejisinin öğrencilerin akademik başarılarına etkisini belirlemek üzere bir meta analiz çalışması yapılmıştır. Bu amaçla Türkiye'de konuyla ilgili 2000-2017 yılları arasında yapılmış olan araştırma problemine uygun çalışmalar; ULAKBİM (Ulusal Akademik Ağ ve Bilgi Merkezi), Yükseköğretim Kurulu Ulusal Tez Merkezi ve Google Akademik veri tabanlarında taranmıştır. Araştırma kapsamında literatür taraması sonucu araştırmaya dayalı öğrenme stratejisinin akademik başarıya et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…According to the results of this study, the effect of IBL on academic achievement is higher at high school level than secondary school and higher education levels. In the meta-analysis study conducted by Sarı and Şaşmaz Ören (2020) on the impact of IBL on academic achievement, the effect size at the secondary school level is higher. However, when the study of Sarı and Şaşmaz Ören (2020) was examined in detail, it was found that there was no sample at the high school level in the study of the researchers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the results of this study, the effect of IBL on academic achievement is higher at high school level than secondary school and higher education levels. In the meta-analysis study conducted by Sarı and Şaşmaz Ören (2020) on the impact of IBL on academic achievement, the effect size at the secondary school level is higher. However, when the study of Sarı and Şaşmaz Ören (2020) was examined in detail, it was found that there was no sample at the high school level in the study of the researchers.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the effect size (ES = 1.147) obtained in the meta-analysis study was high and positive. Sarı and Şaşmaz Ören (2020) determined that the effect size value (ES = 0.70) has a medium effect size and that there is a statistically significant difference given the meta-analysis study conducted in order to determine the effect of IBL on the academic achievement of students. The effect size (ES = 1.029) obtained in the meta-analysis study conducted by Aktamış et al (2016) with the same purpose was high and positive.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are a meta-analysis study (Aktamış, Hiğde, & Özden, 2016;Akkaya, 2019), a literature review (Boğar, 2019), and an evaluation study (Sarı & Şaşmaz-Ören, 2020) related to inquiry-based teaching.…”
Section: çAlışma Deseni Ve öRneklem Seçimimentioning
confidence: 99%
“…Alan yazın incelendiğinde ayrıca araştırmaya dayalı öğretim ile ilgili meta-analiz (Akkaya, 2019; Aktamış, Hiğde ve Özden, 2016), literatür taraması (Boğar, 2019) ve değerlendirme çalışmaları (Sarı ve Şaşmaz-Ören, 2020) yapıldığı belirlenmiş ve bu çalışmalar arasında literatür çalışmasının niceliksel olarak az olduğu gözlenmiştir.…”
Section: Introductionunclassified
“…Ören ve Sarı, 2019;Sarı ve Ören, 2020). Buna rağmen sorgulamaya dayalı öğrenmeye yönelik çalışmaların eğilimlerini belirleyerek bu çalışmaların içeriklerine daha geniş bir bakış açısı sağlamayı amaçlayan içerik analizi çalışmalarının daha sınırlı sayıda olduğu tespit edilmiştir(Kızılaslan, Sözbilir ve Yaşar, 2012; Pedaste ve diğ., 2015; Taş ve diğ., 2019).…”
unclassified